Developmental screening tools for identification of children with developmental difficulties in high-income countries: a systematic review - Cibralic, Sara; Hawker, Patrick; Khan, Ferosa; Lucien, Abbie; Mendoza Diaz, Antonio; Woolfenden, Susan; Murphy, Elisabeth; Deering, April; Schnelle, Clare; Townsend, Sharnee; Eapen, Valsamma (Frontiers in Child and Adolescent Psychiatry, 2023)
Objective To examine and synthesize the literature on the use of universal developmental screening and surveillance tools in high-income countries in relation to (1) psychometric properties; (2) knowledge, acceptability, and feasibility of tools; and (3) follow-up taken following screening/surveillance. Method A PRISMA-compliant systematic review was performed in the PsychInfo, PubMed, and Embase databases. Studies published in the English language were included if they reported results evaluating a universal developmental screening or surveillance measurement tool. Articles on service providers’ and/or parents’ views on developmental screening were also included. Two independent reviewers extracted data and assessed for risk of bias using the Mixed Methods Appraisal Tool and the Quality Assessment of Diagnostic Accuracy Studies Tool. Results were synthesized qualitatively. Results Initial searches identified 2,078 articles, of which 52 were included in the final review. Findings showed that several articles assessing the accuracy of screening tools have been published, and together, they suggest that the accuracy of screening tools varies across cultures and countries. Furthermore, available literature indicated that administering universal developmental screening tools was feasible and acceptable, though only a small number of studies are available. Results also showed a limited number of studies looking at actions taken following positive screening results. Conclusion As the evidence stands, more research assessing the acceptability, feasibility, and accuracy of developmental screeners, is needed. Systematic review registration This review has been registered with the University of York Centre for Reviews and Dissemination (PROSPERO; https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=337320, registration number CRD42022337320).